2002
DOI: 10.1001/archinte.162.22.2605
|View full text |Cite
|
Sign up to set email alerts
|

Is Impaired Renal Function a Contraindication to the Use of Low-Molecular-Weight Heparin?

Abstract: The use of a 30-mL/min (0.50-mL/s) cutoff is not justified, on the basis of currently available evidence, to select individuals at increased risk of accumulation when LMW heparin is used. The pharmacokinetic response to impaired renal function may differ among LMW heparin preparations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(67 citation statements)
references
References 15 publications
0
62
0
5
Order By: Relevance
“…9 Supporting the use of anti-factor Xa monitoring in patients with renal failure is the different potential for accumulation among the various LMWH preparations and the absence of a clear threshold of creatinine clearance for identification of patients at increased risk for accumulation. 41 Obese patients have been under-represented in treatment trials using LMWH, and although individual LMWH preparations have shown predictable antifactor Xa levels in this patient group, 42,43 measuring levels on at least 1 occasion seems prudent.…”
Section: Comparative Efficacy and Safety Of Ufh And Lmwhmentioning
confidence: 99%
“…9 Supporting the use of anti-factor Xa monitoring in patients with renal failure is the different potential for accumulation among the various LMWH preparations and the absence of a clear threshold of creatinine clearance for identification of patients at increased risk for accumulation. 41 Obese patients have been under-represented in treatment trials using LMWH, and although individual LMWH preparations have shown predictable antifactor Xa levels in this patient group, 42,43 measuring levels on at least 1 occasion seems prudent.…”
Section: Comparative Efficacy and Safety Of Ufh And Lmwhmentioning
confidence: 99%
“…A creatinine clearance threshold of 30 ml/min is frequently used to identify patients who may be at increased risk for bioaccumulation and bleeding, although there is no evidence to support this threshold (7). It is understandable, then, that clinical use of LMWH in patients with renal failure has been inconsistent; when used therapeutically, there is variable reliance on monitoring with anti-Xa levels and variable empiric dose adjustments.…”
mentioning
confidence: 99%
“…Renal failure with GFR <30 ml/min limits the use of LMWH, since these drugs depend on renal clearance for drug elimination and increased blood levels increase the risk of bleeding. 47 Whether the occurrence of thromboembolic complications is associated with increased mortality in multiple myeloma is still controversial. Shorter survival was reported in patients with early thrombotic events (within 6 months after start of initial therapy 43 or within the first 2 years 44 ) while in another study 45 no difference in mortality was noted, neither in newly diagnosed nor in relapsed/refractory myeloma.…”
Section: Thromboembolic Complicationsmentioning
confidence: 99%